Advancing Health Behavior Research and Scholarship through Mentorship of First Generation, Underrepresented Undergraduate Students - Daphne C. Hernandez; Lorraine R. Reitzel; Isabel M. Leal (New Prairie Press, 2019)
This article provides perspectives about mentorship of undergraduate mentees from directors of formal, externally funded training programs within the context of one of the most ethnically diverse national universities. The authors reflect about their mentorship of first generation and underrepresented undergraduate students and offer recommendations for others training similar students.